A new vision to repair damages in composite concretes via using the self-healing concrete technologies - Jalili, Sogand; Jalili, Iman (Journal of Composites and Compounds, 2025)
Concrete, as a widely used material in the construction industry, despite its high compressive strength, is prone to cracking due to its weak tensile strength, which leads to a reduction in the durability and lifespan of structures. Self-healing concrete technologies have created a new perspective in improving the sustainability and reducing the maintenance costs of concrete structures by providing innovative and intelligent solutions for automatic crack repair. These technologies, by utilizing natural and engineering mechanisms, promise to increase the lifespan and durability of composite structures. This commentary explores the issue and outlines the promise of self-healing concrete technologies.